2022
DOI: 10.1111/imm.13488
|View full text |Cite
|
Sign up to set email alerts
|

TIM3/CEACAM1 pathway involves in myeloid‐derived suppressor cells induced CD8+ T cells exhaustion and bone marrow inflammatory microenvironment in myelodysplastic syndrome

Abstract: Myeloid-derived suppressor cells (MDSC) induced cellular immune deficiency and bone marrow inflammatory microenvironment play an important role in the pathogenesis and progression of myelodysplastic syndrome (MDS), but the underlying mechanism remains unclear. Here, we revealed that immune checkpoint protein TIM3 and CEACAM1 were highly demonstrated on MDSC and CD8 + T cells in MDS patients. CD8 + T cells were reduced in number and function and presented a exhaustion state. The levels of pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…As a result, numerous neuroin ammation processes further exacerbate the pathological processes that cause cognitive impairment [40]. The in ammatory signaling pathway NF-κB/NLRP3/caspase-1 is activated in a variety of cells [39,41]. In this study, NF-κB/NLRP3 in ammasome activation was found to be involved in neuroin ammation caused by WD feeding.…”
Section: Discussionmentioning
confidence: 63%
“…As a result, numerous neuroin ammation processes further exacerbate the pathological processes that cause cognitive impairment [40]. The in ammatory signaling pathway NF-κB/NLRP3/caspase-1 is activated in a variety of cells [39,41]. In this study, NF-κB/NLRP3 in ammasome activation was found to be involved in neuroin ammation caused by WD feeding.…”
Section: Discussionmentioning
confidence: 63%
“…Tao et al found that CD8+ T-cell exhaustion in MDS was partially dependent upon activation of the T-cell immunoglobulin and mucin-domain containing 3 (TIM3)/Galectin 9 (Gal 9) pathway [ Figure 4 ] and suggested that Gal 9 upregulation by MDSCs is responsible for this activation [ 179 ]. TIM3/Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) pathway activation may also be an alternative mechanism of MDSC involvement in T-cell exhaustion [ 180 ]. Irrespective of the specific mechanisms of MDSC-induced inhibition, MDSCs do not harbor the same mutations as the dysplastic clones [ 174 ], thus constituting an independent cellular component of the microenvironment that is actively involved in MDS pathophysiology.…”
Section: Bm Ime In Mdsmentioning
confidence: 99%
“…An analogous population has been identified by the unsupervised clustering of multidimensional mass cytometry data in patients with MDS [ 83 ]. The expansion of MDSCs has been mainly observed in the patients classified as high risk [ 80 , 81 , 82 , 84 ]. Although it is still an open question under investigation, there is more evidence today, mainly from preclinical models [ 78 , 85 ], that the presence of MDSCs in the BM per se can induce myelodysplastic changes and, therefore, the accumulation of MDSCs in the BM of MDS patients could be of pathogenetic significance contributing to the development and clinical course of the disease, as is discussed in detail in the next section.…”
Section: Expansion and Significance Of Mdscs Derived From Nonmalignan...mentioning
confidence: 99%
“…In line with these data, it has also been reported that the levels of IL-10 and TGFβ1 produced by Lin − /CD33 + / DR − MDSCs are increased in high-risk MDS patients, implying their possible prognostic value in patients with MDS [ 92 ]. Moreover, MDSCs could be themselves cellular sources of proinflammatory cytokines such as IL-1β [ 84 ], contributing to the inflammatory milieu, a well characterized feature of MDS [ 93 ].…”
Section: Mdscs and Immune Dysregulation In The Mdsmentioning
confidence: 99%
See 1 more Smart Citation